2021
DOI: 10.5851/kosfa.2021.e50
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rheological and Sensory Characteristics of Plant-Based Meat Analog with Comparison to Beef and Pork

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This manuscript does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Furthermore, our previous study also confirms our current findings, with the hardness, chewiness, and gumminess of the control being significantly higher compared to the C-TVP and T-ISP of meat analog patties, respectively [14]. The beef patty control exhibited greater hardness and a firmer texture due to muscle protein denaturation in the meat system [37]. The shrinkage and percentage of the thickness of the beef patties made with TVP were significantly reduced (p < 0.05) as the level of TVP increased from 10 to 40%.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…Furthermore, our previous study also confirms our current findings, with the hardness, chewiness, and gumminess of the control being significantly higher compared to the C-TVP and T-ISP of meat analog patties, respectively [14]. The beef patty control exhibited greater hardness and a firmer texture due to muscle protein denaturation in the meat system [37]. The shrinkage and percentage of the thickness of the beef patties made with TVP were significantly reduced (p < 0.05) as the level of TVP increased from 10 to 40%.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…Bakhsh et al [ 41 ] recently revealed that TVP, when used as a major ingredient in hamburgers, had characteristics comparable to those of hamburgers made from beef and pork. However, it was noted in his other study that the surface of the patties that were made from TVP and texturized SPI both had a granular look, which is a downside of employing those two ingredients [ 68 ]. While using chickpea flour and TVP, Sharima-Abdullah et al [ 107 ] produced an imitation of chicken nuggets, which was stated to be a promising product.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most challenging sensory qualities to simulate is the ‘real meat’ texture. This is attributed to the characteristics of whole muscle tissue consisting of muscle fibres, connective tissue and adipose tissues, which are organised into complex ordered structures [ 17,18 ] . Appearance including colour, as well as aroma and flavour are also quite difficult to mimic.…”
Section: Sensory Properties and Challenges For Product Developersmentioning
confidence: 99%
“…One of the main barriers to consumers enjoying sustainable foods is the inferior sensory quality compared to animal‐based products [ 16,17 ] . This is due to differences in the macro composition, i.e.…”
Section: Sensory Properties and Challenges For Product Developersmentioning
confidence: 99%